2004
DOI: 10.1029/2003gb002045
|View full text |Cite
|
Sign up to set email alerts
|

Modeling greenhouse gas emissions from rice‐based production systems: Sensitivity and upscaling

Abstract: [1] A biogeochemical model, Denitrification-Decomposition (DNDC), was modified to enhance its capacity of predicting greenhouse gas (GHG) emissions from paddy rice ecosystems. The major modifications focused on simulations of anaerobic biogeochemistry and rice growth as well as parameterization of paddy rice management. The new model was tested for its sensitivities to management alternatives and variations in natural conditions including weather and soil properties. The test results indicated that (1) varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
206
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 248 publications
(213 citation statements)
references
References 60 publications
(54 reference statements)
7
206
0
Order By: Relevance
“…Flooding has been shown to either promote or reduce CO 2 emissions depending upon land management regime (Aulakh et al 2001;Li et al 2004;Loeb et al 2008). Although a reduction in the production of CO 2 was expected due to the increase in the salinity of soil solution observed when the flooded soil was amended with maize residues (high ratio C/ N; Hasbullah and Marschner 2015), in our experiment, inundation caused little change in net CO 2 emissions.…”
Section: Soil Greenhouse Gas Emissionsmentioning
confidence: 56%
“…Flooding has been shown to either promote or reduce CO 2 emissions depending upon land management regime (Aulakh et al 2001;Li et al 2004;Loeb et al 2008). Although a reduction in the production of CO 2 was expected due to the increase in the salinity of soil solution observed when the flooded soil was amended with maize residues (high ratio C/ N; Hasbullah and Marschner 2015), in our experiment, inundation caused little change in net CO 2 emissions.…”
Section: Soil Greenhouse Gas Emissionsmentioning
confidence: 56%
“…Many studies (Khalil and Butenhoff, 2008;Li et al, 2004;Matthews et al, 2000;Van Bodegom et al, 2002) have suggested that a significant proportion of the uncertainty in regional rice paddy methane emissions arises from data scarcity, especially with regard to SAND, OM, GY, W ptn and VI. The CH4MOD sensitivity analysis similarly indicates the importance of these five factors in methane emissions (Table B1 in Appendix B).…”
Section: Pdfs Of the Model Input Variablesmentioning
confidence: 99%
“…Most of these previous studies focused on organic matter application and water regimes in their estimations of uncertainty (Table 5) because of data scarcity in these two factors. Taking into consideration the tremendous spatial heterogeneity of soil characteristics, Li et al (2004) believed that these were the most sensitive factors accounting for uncertainties, and that the uncertainty was between 2.3-10.5 Tg yr −1 (1.7-7.9 Tg yr −1 C) for mid-season drainage irrigation and 8.5-16.0 Tg yr −1 (6.4-12.0 Tg yr −1 C) when continuous flooding was applied.…”
Section: Methane Emissions From Rice Paddies In China and Their Uncermentioning
confidence: 99%
See 2 more Smart Citations